Serological investigations on the main citrus viruses in Malta - Bonavia Gatt M.; D'Onghia A.M. (Proceedings of the Mediterranean research network on certification of citrus (MNCC): 1998-2001, 2002)
Detection of the main citrus viruses (CTV, CPsV and CVV) was firstly carried out in the main citrus groves of Malta. CTV was not detected whereas CPsV and CVV were the only pathogens and diseases infecting citrus groves.
5. and 6. meeting of the CIHEAM Mediterranean Research Network on Certification of Citrus (MNCC), 2000/10/04-06, Algiers (Algeria) and 2001/10-11/26-01, Cairo (Egypt)